The Capital Asset Pricing Model (CAPM): The History of a Failed Revolutionary Idea in Finance?. (3rd December 2012) - Dempsey, Mike
Abstract : The capital asset pricing model (CAPM) states that assets are priced commensurate with a trade‐off between undiversifiable risk and expectations of return. The model underpins the status of academic finance, as well as the belief that asset pricing is an appropriate subject for economic study. Notwithstanding, our findings imply that in adhering to the CAPM we are choosing to encounter the market on our own terms of rationality, rather than the market's.